2011
DOI: 10.1128/aem.02701-10
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Murine Norovirus 1 by Lactuca sativa during Irrigation

Abstract: Romaine lettuce (Lactuca sativa) was grown hydroponically or in soil and challenged with murine norovirus 1 (MNV) under two conditions: one mimicking a severe one-time contamination event and another mimicking a lower level of contamination occurring over time. In each condition, lettuce was challenged with MNV delivered at the roots. In the first case, contamination occurred on day one with 5 ؋ 10 8 reverse transcriptase quantitative PCR (RT-qPCR) U/ml MNV in nutrient buffer, and irrigation water was replaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…The variations in the length of time required to reach the peak virus concentration may be attributed to the experimental protocol, such as the virus types and inoculation levels, procedures, types of plants, growth stage, integrity of roots, and hydroponic system (18-22, 31, 32). The growth stage of plants in this study was much younger (days 8 to 12), whereas the plants used in previous studies mentioned above were at least 3 weeks old following germination (20,22). It is possible that root growth can increase contact surface with recirculated water; allowing the microgreens to concentrate more viruses in their tissues.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The variations in the length of time required to reach the peak virus concentration may be attributed to the experimental protocol, such as the virus types and inoculation levels, procedures, types of plants, growth stage, integrity of roots, and hydroponic system (18-22, 31, 32). The growth stage of plants in this study was much younger (days 8 to 12), whereas the plants used in previous studies mentioned above were at least 3 weeks old following germination (20,22). It is possible that root growth can increase contact surface with recirculated water; allowing the microgreens to concentrate more viruses in their tissues.…”
Section: Discussionmentioning
confidence: 77%
“…It has been observed that plants that were grown in artificially contaminated hydroponic systems can take up viral pathogens (18)(19)(20)(21)(22)(23)(24). The driving force of water absorption facilitates internalization, and humidity in the plant-growing environment significantly affects transpiration (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported that HuNoV and its surrogates can internalize inside lettuce and spinach plants under normal conditions (28,43,44) and in lettuce under certain biotic and extreme abiotic stress a Numbers in bold indicate a significant effect (P Ͻ 0.05) for that factor. Statistical analyses were performed by two-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses, including norovirus and rotavirus, cause foodborne outbreaks, especially due to their persistence in the environment and their low infectious doses (10 to 100 particles) (7,8). Murine norovirus, Tulane virus, and sapovirus have been found to attach to the surface of or within the tissues of romaine lettuce and strawberries (9)(10)(11)(12)(13), which suggests that preharvest viral contamination is a public health concern. To reduce the incidence of viral foodborne illnesses caused by contaminated produce, it is essential to understand the environmental and agricultural factors that control the stability and, therefore, the infectivity of foodborne viruses.…”
mentioning
confidence: 99%